KREATIVITAS BIRTHDAY SNACK PADA REMAJA PUTRI DI BANDAR LAMPUNG - Rina Milyati Yuniastuti; Jhon Nasyaroeka (Institut Informatika dan Bisnis Darmajaya, 2023)
This service is carried out with the aim of fostering the creativity of young women at Rt 03 LK 1 Sumur Putri Village, Teluk Betung Selatan District, Bandar Lampung in making birthday snacks. which will be given when someone has a birthday. Mix and match snacks must pay attention to the composition of the shape of the snack. This training is carried out based on a mutually agreed time with the young women. With this training, the young women can make contemporary birthday snacks properly and correctly. And hopefully this training will be useful for young women to be more creative in making various forms of birthday snacksKeywords— creativity, birthday snack, young women